Rewiring of the Endocrine Network in Triple-Negative Breast Cancer - Li, Kaixuan; Zong, Dongjiang; Sun, Jianrong; Chen, Danxiang; Ma, Minkai; Jia, Liqun (Frontiers in Oncology, 2022)
Immunohistochemically definition of estrogen/progesterone receptors dictated endocrine feasibility regarding the treatment course in breast cancer. Characterized by the deficient estrogen receptor α, ERα-negative breast cancers were dissociated from any endocrine regimens in the routine clinical setting, triple-negative breast cancer in particular. However, the stereotype was challenged by the retained sensitivity and vulnerability of triple-negative breast cancers to the endocrine agents, wherein the interplay of hormone action and the carcinogenic signaling program was recognized and underscored along with the increasing investigation. The previously overlooked endocrine-responsiveness in ERα-negative breast cancers supplied fresh insight into the therapeutic strategy in an ERα-independent manner. In this review, we elaborated on the steroid hormone actions and endocrine-related pathways in triple-negative breast cancers, which were attached to the label of hormone insensitivity. We also shed light on the non-canonical mechanism detected in the common hormone agents to showcase their pleiotropic effects.